HCV and drug addiction in the historical scenario of infection entry in Italy - Galli, Massimo; Ridolfo, Annalisa; van denBogaart, Lorena; Negri, Cristina; Giacomelli, Andrea (Acta Biomedica Atenei Parmensis, 2018)
The objective of this revision is - through an analysis of the literature – to highlight the relevance and importance of drug addiction in the entry of Hepatitis C virus (HCV) and acquired immunodeficiency (HIV) in Italy, with a review of the history of the HCV various strains that have spread over time through this population (especially in relation to genotypes 3, 4 and in part 1), using the most advanced methods related to the phylogeny and geography of the virus.